A collision tumor composed of colon adenocarcinoma and large cell neuroendocrine carcinoma with gingival metastasis: a case report - Zhang, Zhiqiang; Zhang, Junfeng; Chen, Peng; Kou, Xuexia; Lan, Yunsheng; Jia, Yingdong (Frontiers in Oncology, 2025)
Collision tumors represent a relatively uncommon form of tumor manifestation, characterized by the independent coexistence of multiple distinct types of tumors. Large cell neuroendocrine carcinoma of the colorectum is a rare entity, with limited reports describing collision tumors involving adenocarcinoma and large cell neuroendocrine carcinoma. Distant metastases of colorectal cancer typically occur in sites such as bone, liver, and lungs; however, metastasis to the gingiva is rarely encountered. This paper reports a case of a collision tumor comprising colonic adenocarcinoma and large cell neuroendocrine carcinoma, with accompanying gingival metastasis.